Nutritional Status According to the Short-Form Mini Nutritional Assessment (MNA-SF) and Clinical Characteristics as Predictors of Length of Stay, Mortality, and Readmissions Among Older Inpatients in China: A National Study - Liu, Hongpeng; Jiao, Jing; Zhu, Minglei; Wen, Xianxiu; Jin, Jingfen; Wang, Hui; Lv, Dongmei; Zhao, Shengxiu; Sun, Xiang; Wu, Xinjuan; Xu, Tao (Frontiers in Nutrition, 2022)
Background:Studies are scarce in China that explore the association of nutritional status, measured using the Short-Form Mini Nutritional Assessment(MNA-SF)and biochemical data, on adverse clinical outcomes among older inpatients. In this study, we aimed to determine the prevalence of malnutrition in tertiary hospitals of China and the associations between malnutrition and adverse clinical outcomes. Methods: This prospective study involved 5,516older inpatients (mean age72.47±5.77years) hospitalized in tertiary hospitals between October 2018 and February2019. The tertiary hospitals refer to the hospital with more than 500 beds and can provide complex medical care services. The MNA-SF was used to assess nutritional status. Multiple logistic regression and negative binomial regression were used to analyze the relationship between nutritional parameters and risk of hospital length of stay (LoS),mortality, and rehospitalization. Results: We found that46.19%of hospitalized patients had malnutrition or malnutrition risk, according to the MNA-SF. Death occurred in3.45%of patients.MNA-SF scores0–7(odds ratio[OR]5.738,95% confidence interval [CI] 3.473 to 9.48) were associated with a six-fold higher likelihood of death, and scores8–11(OR3.283, 95% CI 2.126–5.069) with a three-fold higher likelihood of death, compared with MNA-SF scores 12–14 in the logistic regression model, after adjusting for potential confounders. A low MNA-SF score of 0–7(regression coefficient 0.2807,95%CI 0.0294–0.5320; P<0.05) and a score of 8–11(0.2574, 95% CI 0.0863–0.4285; P<0.01) was associated with a significantly higher (28.07% and 25.74%, respectively) likelihood of increased LoS,compared with MNA-SF score12–14. MNA-SF scores 0–7 (OR 1.393, 95% CI 1.052–1.843) and 8–11 (OR 1.356, 95% CI 1.124–1.636) were associated with a nearly 1.5-fold higher likelihood of 90-day readmission compared with MNA-SF scores 12–14 in the logistic regression model. Moreover, hemoglobin level, female sex, education level, former smoking, BMI 24–27.9kg/m2, age 75 years and above, and current alcohol consumption were the main factors influencing clinical outcomes in this population. Conclusions:Malnutrition increases the risk of hospital LoS,mortality,and 90-day readmission. The use of nutritional assessment tools in all hospitalized patients in China is needed. The MNA-SF combined with hemoglobin level may be used to identify older inpatients with a high risk of adverse clinical outcomes. These findings may have important implications for the planning of hospital services.